Age, sex and first treatment of schizophrenia in a population cohort - Kleinhaus, K (2010)
OBJECTIVE: Schizophrenia affects men more than women, but this may not be true at all ages. This study examines the incidence of first hospitalization for treatment of schizophrenia in each sex over different ages. METHODS: We compared the incidence of first admission for treatment in a cohort a cohort of 46,388 males and 43,680 females followed from birth until ages 29-41, using life tables and proportional hazards methods. RESULTS: Life table estimates of cumulative incidence by age 40 were 1.44% in males) and .86% in females. Over all ages the relative risk (RR) in males was 1.6 (95% confidence limits=1.4-1.8) compared with females. Before age 17 there was no significant difference between the sexes (RR=.86, .56-1.3). Excess risk in males was observed only from age 17 (RR=1.7, 1.4-1.9). There was no evidence of the incidence in females catching up with that in males, during the 30s. CONCLUSION: In this population, there was a significant change, over age, in the relative incidence of first hospitalization for schizophrenia between the sexes; the excess incidence in males first developed at age 17.